Artificial Intelligence-Based Crime Prevention Policy in Indonesia - furkan, ali; Susila, M. Endriyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Artificial intelligence (AI) technology has become a major subject in security and privacy issues in the digital era. This article aims to explore the impact of the use of AI technology on crime and law enforcement, with a focus on the Indonesian context. This research uses a descriptive analytical approach to evaluate trends and impacts of using AI in crime prevention. Data was collected through literature studies and analysis of policies and regulations related to AI and law enforcement in Indonesia. The analysis results show that the use of AI technology in law enforcement in Indonesia has increased significantly over the last few years. This is reflected in the number of incidents and controversies involving AI, as well as in the implementation of policies and regulations governing its use. While AI offers great potential in supporting crime investigation and detection, challenges related to privacy, fairness, and accountability also arise as it develops. The use of artificial intelligence technology in law enforcement in Indonesia raises a number of impacts and challenges that need to be considered. Despite its potential to increase the effectiveness of law enforcement, protecting privacy and human rights must be a primary focus in the development and implementation of AI technologies.